(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Today with increasing life expectancy and life span women spend one-third of their life time after menopause. The study aims to investigate Menopausal Symptoms and Quality of Life of Postmenopausal Women Post menopausal women 46 years old and above and residing at Dholka taluka, willing to provide written informed consent and willing to undergo the nursing intervention were included in the study by using Probability sampling method, simple random sampling (lottery method) was used to select the sample. The major conclusion drawn from the study was the intervention found to be effective to minimize the severity of menopausal symptoms and enhance the quality of life of post-menopausal women.